The internationalization of family and non family-owned SMEs - Crick, Dave (Henry Stewart Talks, 2009)
Criteria for classifying family-owned firms, Approaches taken by firms in their internationalization strategies, Factors affecting the internationalization path, Transnational entrepreneurship